Penguatan Peran Kelompoktani Tengger dalam Pengembangan Kapasitas Petani pada Proses Hilirisasi Produk Hortikultura di Wilayah Pegunungan Bromo Jawa Timur - Sudarko, Sudarko; Pradana, Ankardiansyah Pandu; Hariyati, Yuli; Jadmiko, Mochammad Wildan; Savitri, Dyah Ayu (Jurnal KIRANA, 2023)
Strengthening the role of farmer groups in increasing the downstream capacity of farmers is a strategic effort to integrate on farm and off farm level agribusiness systems. This study aims to: (1) analyze the level of the role of farmer groups and the capacity of the downstream process of horticultural agricultural products, and (2) analyze the relationship between the role of farmer groups and the capacity of farmers in the process of off farm level horticultural agricultural products in the Bromo mountain region, Probolinggo Regency. East Java. This research was carried out using a quantitative approach which was carried out at the Horticulture Center in Ngadisari Village, Sukapura District, Tengger Region, Probolinggo Regency in June-August 2023. The population was 70 farmers who were members of 2 farmer groups with a sample of 30 farmers taken using Simple random sampling technique. Primary data the research was taken by interviewing the Likert scale measurement questionnaire and then analyzing it with descriptive and Sperman Rank correlation analysis. The results of the research were: (1) the level of role of farmer groups in increasing farmer capacity in the downstream process is moderate. The capacity of farmers in the off farm level process of horticultural agricultural products is moderate. (2) There is a positive and significant relationship between the role of farmer groups and the capacity of farmers in the off farm process of horticultural agricultural products. It is necessary to strengthen the role of farmer groups in increasing the capacity of farmers in the process of off farm level horticultural agricultural products in the Bromo mountain region, Probolinggo Regency, East Java. Keywords: group roles, farmer capacity, off farm level process, horticultural farmers